2017
DOI: 10.1007/s00705-017-3674-9
|View full text |Cite
|
Sign up to set email alerts
|

The nucleotide sequence of a recombinant tomato yellow leaf curl virus strain frequently detected in Sicily isolated from tomato plants carrying the Ty-1 resistance gene

Abstract: In July 2016, an aggressive syndrome of tomato yellow leaf curl disease was reported in Sicily in tomato plants carrying the Ty-1 resistance gene. A total of 34 samples were collected and analyzed. Twenty-seven out of the 34 samples analyzed appeared to contain only recombinant molecules. One full sequence was obtained after cloning. Alignments and plot similarity analysis showed that the genome of the recombinant, named TYLCV-IL[IT:Sic23:16], was mostly derived from tomato yellow leaf curl virus (TYLCV), with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…The production of infectious DF-640 clones is now underway, and they will be used to verify this hypothesis. Nevertheless, it is well documented that the increase in the acreage of cultivars harboring resistance genes such as Ty -1 can result in strong selection forces towards more aggressive viral isolates, accelerating the change in the composition of the viral population and potentially culminating with the loss of effectivity of the source of resistance/tolerance [ 71 , 72 , 73 , 74 , 75 ]. Studies have also reported the “breakdown” of the resistance mediated by the Ty -2 gene caused by a strain of Tomato yellow leaf curl virus (TYLCV) [ 76 ] and by a strain of the Tomato leaf curl Bangalore virus (ToLCBV) in India [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…The production of infectious DF-640 clones is now underway, and they will be used to verify this hypothesis. Nevertheless, it is well documented that the increase in the acreage of cultivars harboring resistance genes such as Ty -1 can result in strong selection forces towards more aggressive viral isolates, accelerating the change in the composition of the viral population and potentially culminating with the loss of effectivity of the source of resistance/tolerance [ 71 , 72 , 73 , 74 , 75 ]. Studies have also reported the “breakdown” of the resistance mediated by the Ty -2 gene caused by a strain of Tomato yellow leaf curl virus (TYLCV) [ 76 ] and by a strain of the Tomato leaf curl Bangalore virus (ToLCBV) in India [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently several articles have been published on Ty‐1 resistance‐breaking strains of TYLCV in cultivations of Ty‐1 ‐bearing tomato. Samples of Ty‐1 plants showing TYLCV‐like symptoms collected in Morocco, Italy and Spain revealed the presence of viruses derived from a recombination event between TYLCV and TYLCSV in which a noncoding region between the origin of replication and the start of the coding region of V2 were exchanged (Belabess et al , ; Granier et al , ; Panno et al , ; Torre et al , ). In Morocco, this recombinant replaced both parental strains, but also under laboratory conditions this recombinant was positively selected in Ty‐1 ‐bearing plants (Belabess et al , , ).…”
Section: Discussionmentioning
confidence: 99%
“…Among monopartite begomoviruses, the Tomato yellow leaf curl virus (TYLCV) species is an example of an emergent begomovirus that seriously impacts tomato ( Solanum lycopersicum ) production, it causes the tomato yellow leaf curl disease (TYLCD) epidemics throughout the tropical and sub-tropical regions of the world [28]. A large body of information is available about the genetic diversity, biology and worldwide spread patterns of TYLCV [7,29,30,31,32,33,34,35]. In contrast, much less information is available for other begomoviruses also associated with TYLCD epidemics.…”
Section: Introductionmentioning
confidence: 99%